Domestic monetary management in Britain, 1919-38 - Howson, Susan (Cambridge ; New York : Cambridge University Press, 1975)
This book addresses itself to two questions: the reasons for the domestic monetary policies adopted by the Treasury and the Bank of England in the 1920s and 1930s, and the consequences of these policies for the British economy. It also describes in detail the deliberations of the policy makers, particularly those in the Treasury, on those monetary policy decisions that were taken primarily in an attempt to control or combat the severe fluctuations to which the British economy was subject between 1919 and 1939.
Bibliography: p. 206-213.
usc 16/06/17
Loans
Keywords: Monetary policy; Monetary management; Britain